PROBLEMATIKA PENGATURAN PARIWISATA HALAL DI KABUPATEN PAMEKASAN-MADURA - Deni Yuherawan; Eny Suastuti; Uswatun Hasanah (RechtIdee, 2023)
The declaration of the development of halal tourism in Pamekasan still leaves problems. The burning case of a newly established tourist spot in Pamekasan indicates this phenomenon. The purpose of this study is to examine regulations regarding halal tourism in Pamekasan, which is known as the city of the Islamic community development movement (Gerbang Salam) and the problems that arise from the implementation of these regulations. This research is a sociolegal research, using primary data and secondary data. The data obtained were analyzed qualitatively. The results of the study show that in Pamekasan there is a Pamekasan Regency Regional Regulation Number 2 of 2019 as a regulation that regulates the implementation of entertainment and recreation so that it is in accordance with the customary, religious and cultural values of the community. The problem that arises is that there are still differences in perceptions between entertainment managers and the local community, supervisory institutions are not firm in taking action against violations of entertainment and recreation businesses that violate local regulations, giving rise to vigilante actions by the surrounding community.